Optimizing Employee Engagement: Exploring the Role of Perceived Organizational Support and Employee Experience in Logistics Companies - Purnama, Chamdan (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2025)
This research aims to explain the relationship between Perceived Organizational Support (POS), employee experience, and employee engagement (EE) in logistics companies. It also explores how employee experience moderates the relationship between POS and EE. The study uses an explanatory approach to test the proposed hypotheses through multiple regression analysis and Moderated Regression Analysis (MRA). Data was collected from 80 employees in logistics companies using a structured questionnaire based on a five-point Likert scale. The findings reveal that POS has a significant positive influence on EE. Moreover, the results demonstrate that employee experience strengthens the relationship between POS and EE, suggesting that improvements in employee experience can further enhance the positive effect of POS on employee engagement. This study highlights the critical role of fostering POS and enhancing employee experience as effective strategies to boost employee engagement in logistics companies.